Pembelajaran PAI di Perguruan Tinggi Umum - Agus Ali; Uus Ruswandi (Jurnal Dirosah Islamiyah, 2022)
The Islamic religious education learning that has been carried out at the University of Buana Perjuangan Karawang which has been taking place so far is a general course / personality development given to all students, so that students have personality and character values ​​based on the Qur'an and Hadith and have religious insight that comprehensive / comprehensive. Religious Education in Higher Education aims to help foster students who believe and are devoted to God Almighty, have noble character, think philosophically, act rationally, have broad views, participate in developing and utilizing science and technology for the benefit of humans. This study aims to analyze the learning of Islamic religious education at the University of Buana Perjuangan Karawang. To see how PAI teachers learn in public universities. This research focuses on 3 problems, namely: 1) PAI learning content organizing strategies, 2) PAI learning delivery strategies, 3) PAI learning management strategies. This research uses a qualitative approach with the type of case study research. The data collection methods were interviews and documentation, which answered about learning Islamic religious education at the University of Buana Perjuangan Karawang. The informants in this study were PAI lecturers and students..The results of this study are 1) The strategy for organizing PAI learning content used is that the lecturer makes materials and syllabus then submitted to GKM at the Study Program level then GJM at the faculty level and then LP3M for approval. The organization of the material is made from doctrinal materials to materials that are broader and more detailed. In several other courses, books containing material that can be used as learning references are provided and each PAI lecturer is encouraged to make books or learning modules. 2) Online-based PAI learning delivery strategies, namely in the form of zoom meetings or google meetings. 3) PAI learning management strategy is setting lecturers to deliver 2 credits for 90 minutes using Lecture, Discussion, Presentation and Problem Solving techniques. Lecturers motivate student learning by conveying learning objectives in the midst of learning in class. In addition, the lecturer also asked students to read the Qur'an first before the group started the presentation. Keywords: Learning, Islamic Religious Education, Public Universities